An Exploration of the Adolescent Experience of Literacy and Reader Identity in an Urban DEIS Post-Primary School - McNamara, Laura (Trinity College (Dublin, Ireland). School of Education, 2021)
Abstract Laura McNamara An Exploration of the Adolescent Experience of Literacy and Reader Identity in an Urban DEIS Post-Primary School Schools in Ireland have experienced increased focus on the teaching of literacy, with ‘Being Literate’ a key skill for all junior cycle students; it is fundamental to all subjects and core to whole-school planning. Along with this, schools in areas of educational disadvantage have continually been setting and measuring targets in areas such as literacy. Performance on international tests of reading literacy have had a significant impact in directing this focus. There are many reports analysing performance, but few studies that look at how individual schools implement literacy teaching and learning. This case study was conducted by a teacher-researcher in a Delivering Equality of Opportunity in Schools (DEIS) urban post-primary school in Ireland. It seeks to understand the student experience of literacy classes, the reading identities within these, and how these reading identities experience literacy. The study is mostly qualitative, with a small quantitative element in the form of a scale that aims to understand reader self-perception. Data was collected from a survey, literacy autobiographies, and semi-structured interviews. Thematic analysis was used to generate themes from the data. The findings present two major themes from across the data and a third minor theme from the literacy autobiographies and interviews. They are as follows: 1. A Narrow View of Literacy, 2. The Literacy Environment, and 3. A Literacy Learning Path. The three themes are not distinct but interplay with each other. Within the findings, participants self-identified as either ‘readers’ or ‘non-readers’. For all participants, literacy was deeply connected to reading books in the library environment, with vocabulary growth and reading strategies as key literacy skills. Identity played a significant role in the experience of students, with readers having far more positive experiences than non-readers. This is the result of the narrow perspective and definition of literacy. Along with this, literacy practices seemed constrained by a dependence on programmes and interventions, resulting in those who do not read books failing to position themselves in the class or within the meaning of literacy. The findings of this case study suggest that a broader perspective of literacy is needed in the school; one that incorporates multiliteracies, critical literacy, and digital literacy. While access to books, reading for pleasure, and teaching reading strategies is commendable, it does not take a lifespan approach to literacy, considering the literacy needs of adolescents in general and the individual identities within the classroom.
Keywords: Language Education; Education